The effect of yield curve shape and level on bond immunisation effectiveness. Issue 3 (1st September 2016) - Prettejohn, Brendan; van Vuuren, Gary
ABSTRACT: The effect of different-shaped yield curves on the effectiveness of bond immunisation was investigated. Bonds were priced using historical yield curves of various shapes and simulated interest rate shocks applied. The resulting end-values of these bonds were calculated and compared at relevant duration dates using symmetrical (positive and negative) shocks. Yield curve shape and position were found to be important factors for immunisation effectiveness and results also demonstrated that – all else held constant – immunisation effects are asymmetrical for shocks of different sign. Changes in bond value are consistently less pronounced for positive shocks, regardless of yield curve shape or level.